Better lipid target achievement for secondary prevention through disease management programs for diabetes mellitus and coronary heart disease in clinical practice in Germany. (3rd March 2016) - Gitt, Anselm K.; Sonntag, Frank; Jannowitz, Christina; Weizel, Achim; Karmann, Barbara; Schaefer, Juergen R.; Pittrow, David; Hildemann, Steven K.
Abstract: Aims: Disease management programs (DMP) for diabetes mellitus (DM) or coronary heart disease (CHD) address the treatment of lipid disorders. The current registry aimed to compare drug utilization, lipid lowering effects and further outcomes of outpatients at high cardiovascular risk in DMP for DM or CHD compared to patients in routine care (no-DMP). Methods: This was a prospective non-interventional registry with a 1 year follow-up which enrolled consecutive patients with known DM and/or any vascular disease on simvastatin 40 mg monotherapy, to document lipid target achievement in clinical practice in Germany according to existing guidelines. Drug use (maintenance, add-on, switch, discontinuation) and other components of care were upon the discretion of the treating physician. Results: Of a total of 12, 154 patients (mean age 65.8 years, 61.2% males), 3273 were in DMP CHD, 3265 in DMP DM and 1760 in DMP CHD + DM. In DMP patients compared to no-DMP patients, comorbidities/risk factors were more frequent. More patients in the DMP groups attained the target level of low density lipoprotein (LDL-C) <70 mg/dl (1.8 mmol/l) at baseline (8.5% DMP vs. 5.7% no-DMP), at 6 month (10.3% vs. 7.4%) and 12 month follow-up (10.1% vs. 7.1%). Cholesterol absorption inhibitors were added in 16% of the patients at the end of the baseline or at the follow-up visits, while statin treatment (including mean dose) remained largely unchanged. Target achievement rates were highest for all time points in the DMP CHD + DM group. With respect to limitations, this study was restricted to lipid disorders as qualifying diagnosis and simvastatin as qualifying treatment, which is a potential cause of selection bias. Information on non-pharmacological measures was not collected, and the 12-month follow-up period was relatively short. Conclusion: Patients in DMP compared to those not in DMP achieved better LDL-C lowering and higher control rates, but overall lipid target achievement rates need to be improved. Longer-term observations are needed to corroborate these findings.